Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa tentang Menjelajahi Sistem Tata Surya di Kelas VI SD Negeri Nunbaun Sabu - Ndaumanu, Dominika Desryani; Koroh, Taty Rosiana; Ratu, Kurniayu T.R.A. (Lembaga Yasin AlSys, 2025)
This study is motivated by the low learning outcomes of sixth-grade students at SD Negeri Nunbaun Sabu on the topic of exploring the solar system, which has not yet reached the Learning Achievement Criteria (KKTP) of 75. Observational results indicate that the low learning outcomes are due to the teacher-centered learning model, resulting in students being less active and untrained in critical thinking and collaboration. This study aims to improve students' learning outcomes regarding exploring the solar system through the implementation of the problem-based learning model in sixth-grade at SD Negeri Nunbaun Sabu. This type of research is Classroom Action Research (PTK) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Research instruments include observation sheets, learning outcome tests, and documentation. The results of the study show that the implementation of the problem-based learning model can enhance teacher activity, student activity, and learning outcomes. In Cycle I, the average observation score for teacher activity reached 68.3 and student activity 62.5, with a learning completeness of 36.84%. After improvements in Cycle II, the teacher observation score increased to 91.6 and the student score to 87.5, with learning completeness reaching 89.47%. Based on these data, it can be concluded that the implementation of the problem-based learning model in the topic of exploring the solar system can improve students’ learning outcomes. This model makes students more active, critical, and capable of collaborating in problem-solving, and can be used as an alternative learning model to enhance critical thinking skills and learning outcomes in similar subjects.